Evaluation of Hydroalcoholic Extract of Melia Azedarach Linn Roots for Analgesic and Anti-Inflammatory Activity - Vishnukanta; A.C. Rana (International Journal of Phytomedicine, 2010)
Hydroalcoholic extract of Melia azedarach Linn roots were evaluated for analgesic and anti-inflammatory activity in experimental animals. In the doses of 100 and 200 mg/kg, extract inhibited 82.23 % and 88.94 % writhing induced by acetic acid respectively and reduces 15.08 % and 26.45 % paw volume in carageenan induced paw edema.